Quality initiative to improve lung cancer screening in a Veterans Affairs medical center. Issue 28 (1st October 2022) - Miotke, Laura; York, Audrey; Bowles, Alicia; Lewis-Williams, Farrah; Beck, Emily
Abstract : 108 Background: In 2013 the US Preventative Services Task Force recommended lung cancer screening (LCS) with low-dose CT (LDCT) scans in high-risk populations. Eight VA Medical Centers (VAMC) successfully piloted LCS in a demonstration project and several additional VA sites have since launched LCS programs, including the Salt Lake City VAMC. These systems utilize the "Clinical Reminder System" (CRS) in the electronic medical record to enroll patients into the LCS program which allows LDCTs to be tracked by a nurse coordinator. As these programs are relatively new, improvements and shared knowledge is imperative to optimizing the success of LCS programs. Methods: Our intervention was to change the radiology ordering menu to encourage providers to order LDCTs through the CRS, thus enrolling patients in the LCS program. We examined the percentage of LDCTs performed within the LCS screening program as our process measure. We then chose three outcome measures based on recommendations proposed by a national cancer roundtable: 1) Percentage of Lung-RADS 1 or 2 diagnoses with follow-up within 15 months, 2) Percentage of Lung-RADS 3 diagnoses with follow-up within 8 months and 3) Percentage of Lung-RADS 4 diagnoses with follow-up within 18 weeks. We compared outcome measures between LDCTs performed within the LCS program and those performed outside of the program. Results: We compared a total of 492 LDCTs during a pre-intervention six-month period to the 544 LDCTs performed in the first 6 months after our intervention. Pre-intervention, 54% of LDCTs were performed through the LCS program, compared to 79% post-intervention (p < 0.001). The percentage of Lung-RADS 1 or 2 scans with appropriate follow-up time was significantly better within the LCS program (70%), compared to scans performed outside the program (49%, p < 0.001). There was no statistical difference in follow-up of Lung-RADS 3 or 4 scans. Conclusions: Through this work we learned the CRS is non-intuitive and used with variable comfort within the VAMC. As such, a simple intervention guiding ordering providers from the radiology ordering menu to the CRS was effective in increasing enrollment and adherence to follow up in a VA system LCS program. LCS is complex compared to other cancer screening programs. Many primary care providers and radiologists alike are uncomfortable managing these patients. As such, enrollment in a standardized LCS program and early involvement of a multi-disciplinary team is imperative. Not only did we demonstrate this with our outcome measures, but while examining the system we uncovered many inappropriate follow-up scans, biopsies, and oncology consults that contribute to waste. As lung cancer screening programs continue to evolve, quality improvement projects such as this will help improve lung cancer care and outcomes.